The impact of M&A on the operating performance: An empirical analysis of the Professional Services Industry - Xu, Wanting (2013)
Backgrounds: Facing the rising tide of globalisation, firms cannot only compete with domestic counterparts. Companies should keep up with cross-border competitors in the circumstances nowadays. The strong demands for searching internal and external improvements encourage companies which include firms in professional services industry to participate in M&A activities which are increasingly applied nowadays. However, the impact of M&A of professional services has not been researched enough. Methods: In order to explore the influences of M&A activities on operating performance in the professional services industry, primary data and analytical discussion were obtained from Zephyr. Several tests are applied to detect the effects of M&A. Further regression analyses of recent M&A events were conducted by using STATA to arrive at the conclusion. Purpose: This thesis makes an attempt to explore whether M&A can bring improvements for acquirer and target firms or not, and how M&A and financial related factors can affect the operating performance. Findings: M&A activities can negatively affect the operating performance of both bidding and target firms. Factors such as firm size and pre-merger performance are positively correlated with post-merger operating performance, while deal value, market capitalisation and operating revenue can negatively influence post-merger operating performance. Country elements which refer to geographic distribution are not related with operating performance. Keywords: M&A, acquirer, target, financial factors, professional services